Self-supported β-Ga2O3 nanowires and for stretchable solar-blind UV photodetectors - Wuxu Zhang; Ziyin Xiang; Tengfei Ma; Baoru Bian; Jinyun Liu; Yuanzhao Wu; Yiwei Liu; Jie Shang; Run-Wei Li (Scientific Reports)
Abstract Fire rescue robots equipped with solar-blind UV photodetectors can significantly improve operational safety and efficiency in hazardous environments involving high temperatures, explosions, toxic gases, and smoke. However, conventional rigid photodetectors cannot meet the flexibility requirements for seamless integration with robotic systems. This study presents a breakthrough in developing stretchable solar-blind UV photodetectors through an innovative combination of electrospinning and high-temperature phase transformation. Our approach enables high-yield production of self-supporting β-Ga₂O₃ nanowires with excellent solar-blind UV absorption. The fabricated metal-semiconductor-metal (MSM) photodetector demonstrates outstanding performance, including a remarkable photo-to-dark current ratio of 147.2 and responsivity of 22.5 mA/W. More importantly, the device exhibits unprecedented mechanical stability, with merely 3.4% photocurrent variation under 50% tensile strain and only 3.9% degradation after 500 strain cycles. We further demonstrate the practical applicability of this technology by fabricating a functional photodetector array capable of solar-blind UV imaging, paving the way for next-generation intelligent firefighting systems.